海南岛万泉河口海岸动态及其整治对策 - 高建华 陈国强 欧维新 ZHUDakui (Journal of geographical sciences, 2004)
In this paper, sediment samples were collected along the Wanquan beaches and sieved in the laboratory in order to obtain the grain size distributions and associated parameters, i.e. mean grain size,sorting coefficient and skewness. Furthermore, we have calculated the longshore drift sediment transport rates and equilibrium cross-sectional areas of the entrance channel by using the method of sedimentary dynamics. The results indicate that the longshore drift sediment transport is dominated by waves with a direction from south to north, which result in rapid changes of the entrance channel.Therefore, some suggestions were proposed for improving the water quality and restoring the ecosystem of estuary. The engineering method includes increasing the sea-route of entrance channel,tidal prism and water exchanges in Shamei Lagoon.